ФЕНОМЕНОЛОГІЯ ВЗАЄМОЗВ'ЯЗКУ ОСВІТИ І КУЛЬТУРИ ЯК МЕТОДОЛОГІЧНА ОСНОВА ПОЛІКУЛЬТУРНОЇ НАПРЯМОК ОСВІТИ (Педагогіка вищої та середньої школи, 2002)
As a result of the carried-out theoretical analysis is shown, that phenomenology enables to establish history-logic, the reason sequence, functional, remedial, substantial, and other aspects of interrelation of education and culture, which is the basis for modeling a multicultural orientation of education. In view of this the cultural model of high education in a context of culture includes the following conditions: openness of education to the future; integration of all ways of development by the man of the world; development and inclusion in processes of education of performances about integrity of the man, nature, society; personality-guided multicultural orientation of education; organization educational process on ideas of cooperation. It is the basic and important moment in the development of the modern cultural concept of education.